The Transformation of the Institute in the First Decade of the Twenty-First Century: The Unity of Research and Policy Advice. The Realignment of DIW Berlin - Alexander Kritikos; Günter Stock; Klaus F. Zimmermann (Global Labor Organization (GLO), 2025)
This article highlights the transformation of the German Institute for Economic Research ("DIW Berlin") toward a strong dedication to evidence-based policymaking during the first decade of the 21st century and is part of its centennial celebrations in 2025. This shift came in response to a directive by the German Council of Science and Humanities ("Wissenschaftsrat") to all German economic research institutes. DIW Berlin's successful transition was driven in large part by the integration of research and policy advice, as anchored by stringent publication requirements for research staff members.
Keywords: A11; C54; D02; E02; E61; 330; DIW Berlin; evidence-based policymaking; refereed journal publications; Wissenschaftsrat